Combination immunotherapy using G-CSF and oncolytic virotherapy reduces tumor growth in osteosarcoma. Issue 3 (18th March 2021) - Morales-Molina, Alvaro; Gambera, Stefano; Leo, Angela; García-Castro, Javier
Abstract : Background: Osteosarcoma is the most common malignant solid tumor that affects bones, however, survival rates of patients with relapsed osteosarcoma have not improved in the last 30 years. Oncolytic virotherapy, which uses viruses designed to selectively replicate in cancer cells, has emerged as a promising treatment for solid tumors. Our group uses mesenchymal stem cells (MSCs) to transport oncolytic adenoviruses (OAds) to the tumor site, a therapeutic strategy called Celyvir. This treatment has been already applied in human patients, canine patients and different mouse models. In parallel, previous results have probed that administration of granulocyte-colony stimulating factor (G-CSF) increased immune infiltration in tumors. We then hypothesized that the mobilization of immune cells by G-CSF may increase the antitumor efficacy of Celyvir treatment by increasing the immune infiltration into the tumors. Methods: In this study, we use a murine version of Celyvir consisting in murine MSCs carrying the murine OAd dlE102—here called OAd-MSCs—in an immunocompetent model of osteosarcoma. We tested the antitumoral efficacy of the combination of OAd-MSCs plus G-CSF. Results: Our results show that treatment with OAd-MSCs or the union of OAd-MSCs with G-CSF (Combination) significantly reduced tumor growth of osteosarcoma in vivo. Moreover, treated tumors presented higher tumor infiltration of immune cells—especially tumor-infiltrating lymphocytes—and reduced T cell exhaustion, which seems to be enhanced in tumors treated with the Combination. The comparison of our results to those obtained from a cohort of pediatric osteosarcoma patients showed that the virotherapy induces immunological changes similar to those observed in patients with good prognosis. Conclusions: The results open the possibility of using cellular virotherapy for the treatment of bone cancers. Indeed, its combination with G-CSF may be considered for the improvement of the therapy.